The Role of the Prudential Supervision and Financial Restructuring of Banks During Transition to Indirect Instruments of Monetary Control. (IMF Working Papers; Working Paper ;, 1996)
This paper proposes a stylized sequencing of banking supervision and bank restructuring measures designed to complement and expedite the adoption of indirect instruments of monetary policy. Appropriate sequencing reflects both operational considerations and macroeconomic effects of structural measures. It typically involves implementing initially a critical mass of reforms of prudential supervision and of financial structure of both banks and enterprises, and subsequently adapting and refining these measures in line with the evolution of markets and internal governance. This approach facilitates implementation because the initial cost of bank restructuring can be offset, partly, through the budgetary effects of improved enterprise finances.